Pengukuran Indeks Pembangunan Literasi Masyarakat (IPLM) Kota Salatiga sebagai Dasar Penyusunan Program Pengembangan dan Pembinaan Perpustakaan - Warsito, Budi; Rachman Hakim, Arief; Fatmawati, Endang (Jurnal Pustaka Ilmiah, 2023)
The development of public literacy in Indonesia is very dependent on several aspects of people’s reading skills. In determining program development policies and indicators of success, periodic reviews and benchmarks are required. The formulation of the Community Literacy Development Index measurement needs to be done in Salatiga City. The CLDI research aims to determine the value of CLDI in Salatiga City, such as the condition of all types of libraries, both from the aspect of library distribution, collections, library staff, to users in Salatiga City. CLDI measurements were carried out using a census approach. From the results of the research, the score for the Salatiga City CLDI in 2023 was 81.21%. It can be concluded that the score of 81.21% is in the interval between 80 and 90 so the CLDI of Salatiga City in 2023 is included in the high level.